In silico drug repurposing for filarial infection predicts nilotinib and paritaprevir as potential inhibitors of the Wolbachia 5′-aminolevulinic acid synthase - Alexander Kwarteng (Nature Portfolio, 2021)
Abstract Filarial infections affect millions of individuals and are responsible for some notorious disabilities. Current treatment options involve repeated mass drug administrations, which have been met with several challenges despite some successes. Administration of doxycycline, an anti-Wolbachia agent, has shown clinical effectiveness but has several limitations, including long treatment durations and contraindications. We describe the use of an in silico drug repurposing approach to screening a library of over 3200 FDA-approved medications against the filarial endosymbiont, Wolbachia. We target the enzyme which catalyzes the first step of heme biosynthesis in the Wolbachia. This presents an opportunity to inhibit heme synthesis, which leads to depriving the filarial worm of heme, resulting in a subsequent macrofilaricidal effect. High throughput virtual screening, molecular docking and molecular simulations with binding energy calculations led to the identification of paritaprevir and nilotinib as potential anti-Wolbachia agents. Having higher binding affinities to the catalytic pocket than the natural substrate, these drugs have the structural potential to bind and engage active site residues of the wolbachia 5′-Aminolevulinic Acid Synthase. We hereby propose paritaprevir and nilotinib for experimental validations as anti-Wolbachia agents.